Anhaltsmonitoring der tätigkeit der örtlichen haushalte - Shyshkova, Nataliia; Nebieridze, Davyd (My University, 2016)
Abstract. The problems of financial independence of local budgets were analyzed. The structure of expenditures of local budgets of Ukraine was investigated. The key indicators of the organization and the functioning of local budgets were found. The organizational process of monitoring and algorithm of monitoring of the activity of local budgets were given.
Keywords: Key words: local budgets, local government, structure of local expenditures, system of local finance